Comparing the effects of plyometric and isometric strength training on dynamic and isometric force-time characteristics - Lum, Danny (2021)
The purpose of the study was to compare the change in dynamic and isometric force-time characteristics after plyometric (PLYO) or isometric strength training (ISO). Twenty-two endurance runners (age = 37 ± 6 years, stature = 1.71 ± 0.05 m, body mass = 62.7 ± 8.6 kg, weekly mileage = 47.3 ± 10.8 km) performed a countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) test during pre- and post-tests. They were then randomly assigned to either PLYO or ISO group and completed 12 sessions of intervention over six weeks. The PLYO included drop jump, single leg bounding and split jump, and the ISO included IMTP and isometric ankle plantar flexion. Significant and large time x group interactions were observed for CMJ countermovement depth (P = 0.037, ƞ2p = 0.21) and IMTP and relative peak force (PF) (P = 0.030, ƞ2p = 0.22). Significant and large main effects for time were observed in CMJ height, peak power, propulsive phase duration, countermovement depth, reactive strength index modified, IMTP PF and relative PF (P < 0.05, 0.20 ≤ ƞ2p ≤ 0.65). Effect for time showed small improvement in CMJ height for both PLYO (P < 0.001, d = 0.48) and ISO (P = 0.009, d = 0.47), small improvement in CMJ PP in PLYO (P = 0.020, d = 0.21), large increase in countermovement depth (P = 0.004, d = 1.02) and IMTP relative PF (P < 0.001, d = 0.87), and moderate increase in propulsive phase duration (P = 0.038, d = 0.65) and IMTP PF (P < 0.001, d = 0.55) in ISO. There were large differences between groups for percentage change in countermovement depth (P = 0.003, d = 0.96) and IMTP relative PF (P = 0.047, d = 0.90). In conclusion, both PLYO and ISO improved CMJ jump height via different mechanisms, while only ISO resulted in improved IMTP PF and relative PF.